Preparation and fracture mechanism study of graded mechanics bionic resin-ceramic composites in prosthetic dentistry - Shihua Huang; Mingyang Chen; Yichen Xu; Zhou Zhu; Jian Wang; Xibo Pei; Senlin Chen; Ruyi Li; Qianbing Wan (Journal of Materials Research and Technology)
Objective: This study aimed to develop mechanically biomimetic sodium aluminosilicate-based polymer-infiltrated ceramic networks (sa-PICNs) for abutment protection. Methods: Three sa-PICNs with varying ceramic framework porosities were fabricated by varying pressures (250 MPa–300 MPa) and sintering temperatures (800 °C‒850 °C). Mechanical properties were assessed using Vickers hardness and three-point bending tests. The corresponding stress distribution and transmission path were analyzed using digital image correlation (DIC). Based on the obtained data, coarse-graining modeling were performed to further predict the mechanical behavior of nine sa-PICN models with porosities ranging from 10 % to 51 %. Results: sa-PICNs with 25 % (L group), 38 % (M group), and 51 % (H group) framework porosity were prepared. The L and M group exhibited Young's modulus of 24.06 GPa and 17.98 GPa, respectively, similar to that of natural dentin. Vickers hardness of the L group (406.59 HV) was comparable to natural enamel (409.02 HV). The bending deformation was increased by at least 1.4 times after resin infiltration. Coarse-grained simulations revealed widespread cracking occurred with 10 %–15 % porosity and enhanced crack resistance at 15 %–40 % porosity. However, at 40 %–51 % porosity, crack energy mainly dissipated through single large cracks. Predicted Young's modulus and fracture loads for 20 % and 30 % sa-PICNs were 29.16 GPa and 196.31 MPa, and 26.38 GPa and 174.63 MPa, respectively. Conclusion: sa-PICN with 20 %–30 % ceramic framework porosity demonstrated biomimetic mechanical performance and improved crack resistance, suggesting their suitability for prosthodontic applications. Clinical significance: Biomimetic materials can disperse occlusal stresses and provide enhanced protection for abutments in dentistry.